Orientation towards knowledge management applications in service organizations: From the point of view of telecom operators’ Comparative study managers in Algeria - Ilyes BOUDIAF (Journal of North African Economies, 2025)
This study aims to measure the differences in Knowledge management indicators between telecom operators in Algeria. On the basis of three approaches; the descriptive, inductive and comparative approach. We tried to answer the main question and carry out the empirical study. We applied on sample of 67 agencies and use some short interviews with managers, as well as some reports about telecoms market published by ARPCE. To test the hypothesis, we use the one-way ANOVA test. Finally, we have found that there are no significant differences between telecom operators in developing the Knowledge management indicators.